Heat roadmap China: New heat strategy to reduce energy consumption towards 2030. (1st March 2015) - Xiong, Weiming; Wang, Yu; Mathiesen, Brian Vad; Lund, Henrik; Zhang, Xiliang
Abstract: District heating is regarded as a key element of energy saving actions in the Chinese national energy strategy, while space heating in China is currently still dominated by coal boilers. However, there is no existing quantitative study to analyse the future heat strategy for China. Therefore, it is critical to formulate a development strategy to decrease energy consumption and carbon emissions. In this paper, the following three heat strategies are simulated with the energy modelling tool EnergyPLAN: the current heat strategy, an individual heat strategy and a new district heating strategy. These are compared to each other from the national energy system perspective. The comparison of the three strategies indicates that the new district heating strategy which introduces surplus heat from industry and generation plants is more economically and technically optimal than the individual heat strategy and the current heat strategy. The results show that district heating could contribute to a decrease in energy consumption for building heating by about 60% with 15% lower heating cost compared with the current, implemented heat strategy. Highlights: New district heating strategy is designed for China. The new strategy is compared with individual heat and current heat strategy. New strategy could save primary energy supply by ∼60% with 18% lower cost.